Satire in Pandji Pragiwaksono's Pragiwaksono Solo Comedy - Fauzan Nur Faqih; Sintowati Rini Utami; Siti Ansoriyah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2024)
This study aims to describe the satire on “Pragiwaksono” stand-up comedy by Pandji Pragiwaksono. This study uses a qualitative descriptive method with content analysis techniques, namely describing the satire on “Pragiwaksono” stand-up comedy by Pandji Pragiwaksono. The results of the research can be seen that there are 431 data of satirical purposes which are divided into 93 data of correcting purposes (21,57%), 46 data of triggering anger purposes (10,67%), 109 data of quipping purposes (25,30%), 104 data of criticizing purposes (24,13%), and 79 data of pursuing something, person, institution, or event purposes (18,33%). There area 346 data of satirical type which are divided into 152 data of direct satire type (43,93%), 41 data of parody type (11,86%), 27 data of irony type (7,81%), 103 data of sarcasm type (29,76%), and 23 data of exaggeration type (6,64%). There are 149 data forms of satire which are divided into 144 data of satirical clauses/sentenes (96,64%) and 5 data of satirical words/phrases (3,36%).